2002
DOI: 10.1016/s1010-7940(01)01133-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of acute traumatic rupture of the thoracic aorta a timing reappraisal?

Abstract: The immediate outcome of patients suffering from acute traumatic aortic rupture strongly depends on the associated injuries. In some cases, the emergency aortic repair must be favorably delayed because of the necessity of life-sustaining measures and management of major coexisting injuries, which could be worsened by the use of CPB. Conversely, the risk of paraplegia is significantly reduced by the use of CPB and distal perfusion during the time of aortic cross-clamping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…In this study, however, endovascular repair was performed immediately after trauma or as early as possible. Langanay et al reported 20% of 50 patients with delayed surgical treatment between 6 and 60 days because of late diagnosis or coexisting life-threatening lesions without further aortic rupture or sudden death [17].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, however, endovascular repair was performed immediately after trauma or as early as possible. Langanay et al reported 20% of 50 patients with delayed surgical treatment between 6 and 60 days because of late diagnosis or coexisting life-threatening lesions without further aortic rupture or sudden death [17].…”
Section: Discussionmentioning
confidence: 99%
“…Duwayri and colleagues are in accordance with the above authors and advocate delayed repair in hemodynamically stable patients as this was not associated with increased risk of aortic rupture in their small study in 2008 [37]. Surgery was delayed (>24 h) in 6 out of 9 patients who were hemodynamically stable and mortality in this group was zero [38].…”
Section: Evidencementioning
confidence: 52%
“…Multiple trauma patients have always been challenging with regards to the right order and timing of different interventions. A widely accepted definition of delayed repair does not exist in the literature; studies have used different timeframes to define their ''delayed repair'' group such as 16 h, 24 h, 72 h or even a few days post-injury [35][36][37][38][39].…”
Section: Evidencementioning
confidence: 99%
See 2 more Smart Citations